The Bible of Options Strategies: The Definitive Guide for Practical Trading Strategies - Cohen, Guy (Financial Times Prentice Hall books., 2005)
"Guy Cohen is the master when it comes to taming the complexities of options. From buying calls and puts to iron butterflies and condors, Guy explains these strategies in a clear and concise manner that options traders of any level can understand. His chapter on options and taxes is especially welcomed (and needed). The Bible of Options Strategies is a straightforward, easy-to-use reference work that should occupy a space on any options trader's bookshelf." -Bernie Schaeffer, Chairman and CEO, Schaeffer's Investment Research, Inc. "The author delivers clarity, insight and perception making learning about options a joy, and practicing the art of making money that much easier: truly a bible from a guru." -Alpesh B. Patel, Author and Financial Times Columnist "Guy Cohen truly makes learning about options easy in this fact-filled guide. Bullet points make for a quick and enlightened read, getting to the heart of what you really need to know about each options strategy. This book is a must for any serious trader's library." -Price Headley, Founder, BigTrends.com Pick the right options strategies...implement them step-by-step...maximize your profits! Introducing today's first and only comprehensive reference to contemporary options trading! OptionEasy creator Guy Cohen identifies today's popular strategies...and tells you exactly how and when to use each one and what hazards to look out for! It's all here.... Basic Strategies including Buying and shorting shares, calls, and puts. Income Strategies including Covered Call, Naked Put, Bull Put Spread, Bear Call Spread, Long Iron Butterfly, Long Iron Condor, Calendar Call, Diagonal Call... Vertical Spreads including Bull Call Spread, Bull Put Spread, Bear Call Spread, Bear Put Spread, Ladders... Volatility Strategies including Straddle, Strangle, Guts, Short Butterflies, Short Condors... Sideways Strategies including Short Straddle, Short Strangle, Short Guts, Long Butterflies, Long Condors... Leveraged Strategies including Call Ratio Backspread, Put Ratio Backspread, Ratio Spreads... Synthetic Strategies including Collar, Synthetic Call, Synthetic Put, Synthetic Straddles, Synthetic Futures, Combos, Box Spread... ...and many more strategies... Plus essential tax-saving information, and more! No other book presents this much authoritative, current information on options trading strategies Covers all of today's best income, volatility, leveraged, synthetic, and sideways market strategies Discover why eac...